Divine Laughter Preaching and the Serious Business of Humor. - Jacobson, Karl N. (Working Preacher Ser., 2022)
The authors look closely at both the cultural phenomenon of stand-up comedy and theories of humor, asking what preachers can learn from both. Stand-Up Preaching brings the task of preaching into conversation with both the comedic parts of the Bible and the theological parts of the comedic in order to bring a new kind of life to preaching.